MULTICULTURALISM IN EDUCATION INSTITUTION: STUDY ON MULTICULTURALISM PRACTICE IN WIJAYA KUSUMA ELEMENTARY SCHOOL LASEM – REMBANG - Amirudin, Amirudin (HUMANIKA, 2018)
RESEARCH - is conducted to examine how multiculturalism is carried out in the field of educational. This research is intended to create a learning model that is able to produce multicultural products in Elementary School. Through ethnographic methods, this study found that the  multiculturalism practice in SD Wijayakusuma had happened, it can be seen by the dynamic interaction between inclusive actors. Elementary school students are openly abled to interact others without distinguishing ethnicity, religion, race and class. They have relation just the way they are, self openess, all students can be friends with anyone and express themselves without fear of threats from any parties.Good interaction have been seen among students then create mutual appreciation and respect each others. In addition, this research also found that the factor that support multiculturalism creation in research locations such as: foundation policies and school’s key person who develop schools without any limitation of religion, ethnicity, culture, mutual appreciation and respectfull.Meanwhile, other supporting factors are: infrastructure facilities for extracurricular cross ethnic activities; school changing name, free uniforms on Friday, teacher who have a sense of tolerance toward student, non-discriminatory school rules, meetings or deliberation between school and parent, mix-cultural arts between Javanese and Chinese, celebrating religious holidays, helping each other in preparation for religious activities, as well as the people enthusiasm who were very enthusiastic about the school.Based on the findings, the researcher suggested: schools must provide more inclusive service space without discriminating between students. Improving the student facilities needed, holding joint activity that entertain community to show mutual appreciation and respect people each other. Even though they are different, they can still communicate each other. That’s why people put great expectation and abled give full support to the institutional of SD Wijayakusuma.